The Korean Version of the Barkley Deficits in Executive Functioning Scale: 성인 주의력결핍 과잉행동장애에서의 유효성 연구 - 최지승, 이원혜, 안호원, 김지혜, 정유숙, 이근희(Keun hee (Singyŏng chŏngsin ŭihak, 2020)
Objectives To identify the clinical utility of the Korean version of the Barkley Deficits in Executive Functioning Scale (K-BDEFS) assessing executive functioning. Methods The patient group included 144 adult attention-deficit/hyperactivity disorder (ADHD) patients visiting the Adult ADHD Outpatient Clinic of the National Center for Mental Health. Adult ADHD Self-Report Scale version 1.1, Mini International Neuropsychiatric Interview, and K-BDEFS were used. The control subjects were 144 age, sex, and education-matched general adults who participated in the study of the validity of the K-BDEFS in Samsung Medical Center. Results An analysis of the mean total K-BDEFS score, executive functioning symptom count, and ADHD-executive function (EF) index score revealed a significant difference between the adult ADHD and control group (p<0.05). Five subscales of the K-BDEFS, which assess the specific domains of the executive function, revealed a significant difference between the ADHD group and control group (p<0.05). The area under curve (AUC) of the K-BDEFS total score, the EF symptom count, and the ADHD-EF index were 0.943, 0.949, and 0.908, respectively, in the analysis using the receiver operating characteristic curve. All AUC values were over 0.90. Therefore, KBDEFS is a reliable and valid screening instrument for diagnosing adult ADHD. In an assessment of the sensitivity and specificity of the cutoff scores, a cutoff of 183.5 points for the K-BDEFS total score, 26.5 points for the EF symptom count, and 23.5 points for the ADHD-EF index showed a reliable sensitivity and specificity above 80%. Conclusion To the best of the authors’ knowledge, this is the first study to examine the predictive validity and clinical utility of K-BDEFS in adult ADHD. The results suggest that the K-BDEFS could be used as a valid and reliable tool for the diagnosis and clinical intervention of adult ADHD. KCI Citation Count: 0